1994
DOI: 10.2307/820555
|View full text |Cite
|
Sign up to set email alerts
|

Using Portfolio Reflections to Re-Form Instructional Programs and Build Curriculum

Abstract: . Using portfolio reflections to re-form instructional programs and build curriculum. English Journal, 83(7), 71.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

1995
1995
2017
2017

Publication Types

Select...
3
1

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 0 publications
0
2
0
Order By: Relevance
“…Curriculum was another factor that Maeroff (1991) and Robbins et al (1994) shed light on. They reported that students get clear guidelines and tips to guide them in the process of implementing the portfolios.…”
Section: Factors That Facilitate the Implementation Of The Student's mentioning
confidence: 99%
See 1 more Smart Citation
“…Curriculum was another factor that Maeroff (1991) and Robbins et al (1994) shed light on. They reported that students get clear guidelines and tips to guide them in the process of implementing the portfolios.…”
Section: Factors That Facilitate the Implementation Of The Student's mentioning
confidence: 99%
“…That might save teachers' and students' time by depending on some of these activities instead of designing all the activities by themselves. In addition, there had to be stated guidelines and tips for both teachers and students to guide them in implementing the portfolio (Maeroff, 1991;Robbins, Brandt, Goering, Nassif, &Wascha, 1994). …”
Section: Research Questionsmentioning
confidence: 99%